Evaluation of cardamom (Elettaria cardamomum Maton) germplasm - Joseph, N Miniraj, M Murugan, Cannel Rani (Journal of Spices and Aromatic Crops, 2000)
Seventy two cardamom (Elettaria cardamomum) accessions were evaluated for 5 years at Pampadumpara (Kerala, India) for vegetative and economic characters and susceptibility to insect pests. Nine accessions recorded a dry capsule yield of above 150 g per clump. Among these nine promising accessions, S-1 appeared to be the best for further breeding programmes in view of its higher yield, moderate incidence of insect pests and higher quality parameters compared to other entries. Accessions MBP (Multiple Branching Panicle) and CP (Compound Panicle) can also be used in breeding programmes in view of their higher yield potential. The entries PS-12 and PS-5 offer great scope in breeding for quality.